2016
DOI: 10.1177/0731684416648780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness on the impact resistance of flax fibre-reinforced polymer

Abstract: Impact properties of flax fibre-reinforced polymer composites were investigated using two different impact test methods, i.e. drop-weight test and Charpy test. The drop-weight impact tests were conducted with varying drop height. For the drop-weight tests, the perforation energy and the energy absorbed by a specimen are used to study the impact response of the flax fibre-reinforced polymer composite. In a series of Charpy tests, the energy absorbed per unit width of the specimen was investigated. Impact force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…The ductility index decreased as the composite thickness increased. [385] Saidane et al investigating the hybridization effect on the diffusion kinetics and the tensile mechanical behavior of flax-glass fibers reinforced epoxy composites. The obtained results showed that the addition of glass fiber layers into the flax laminate clearly…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…The ductility index decreased as the composite thickness increased. [385] Saidane et al investigating the hybridization effect on the diffusion kinetics and the tensile mechanical behavior of flax-glass fibers reinforced epoxy composites. The obtained results showed that the addition of glass fiber layers into the flax laminate clearly…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…Thick composites are less vulnerable to impact damages than thin composites. Wang et al [231] investigated the low-velocity impact response of flax reinforced composites. They reported that contact force and Hertzian force increased and ductility index reduced as the thickness increased.…”
Section: Thicknessmentioning
confidence: 99%
“…The predominant failures were determined during the impact event, mainly by the composite laminate thickness [172]. Therefore by considering thickness in NFPC composites, Wang et al [173], noticed that impact force and the Hertzian force of flax -fibre reinforced polymer was found to increase with increasing thickness. Whereas the ductility index decreases with increased composite thickness.…”
Section: Thicknessmentioning
confidence: 99%